Pendekatan Moneter dalam Analisis Neraca Pembayaran Internasional: Teori dan Aplikasinya - Kartika Marliana Sulistiara Pramesti; Royyan Quwais Al-Qarni; Sarpini (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
The monetary approach in international balance of payments analysis offers a theoretical framework that emphasizes the role of money markets in determining a country's external balance. This approach is based on the principle that balance of payments imbalances reflect imbalances between the demand and supply of money in domestic and international markets. This article discusses the basic theory of the monetary approach, including the implications of changes in foreign exchange reserves, interest rate movements, and their impact on the exchange rate. In addition, this research explores the empirical application of the monetary approach in various global economic contexts. Case studies show how monetary policy influences balance of payments dynamics, exchange rate stability and capital flows. These findings provide strategic insights for economic policymakers to design policies that support macroeconomic stability while encouraging sustainable growth.